Applications of Zeolites to C1 Chemistry: Recent Advances, Challenges, and Opportunities. Issue 44 (22nd July 2020) - Zhang, Qiang; Yu, Jihong; Corma, Avelino
Abstract: C1 chemistry, which is the catalytic transformation of C1 molecules including CO, CO2, CH4, CH3 OH, and HCOOH, plays an important role in providing energy and chemical supplies while meeting environmental requirements. Zeolites are highly efficient solid catalysts used in the chemical industry. The design and development of zeolite‐based mono‐, bi‐, and multifunctional catalysts has led to a booming application of zeolite‐based catalysts to C1 chemistry. Combining the advantages of zeolites and metallic catalytic species has promoted the catalytic production of various hydrocarbons (e.g., methane, light olefins, aromatics, and liquid fuels) and oxygenates (e.g., methanol, dimethyl ether, formic acid, and higher alcohols) from C1 molecules. The key zeolite descriptors that influence catalytic performance, such as framework topologies, nanoconfinement effects, Brønsted acidities, secondary‐pore systems, particle sizes, extraframework cations and atoms, hydrophobicity and hydrophilicity, and proximity between acid and metallic sites are discussed to provide a deep understanding of the significance of zeolites to C1 chemistry. An outlook regarding challenges and opportunities for the conversion of C1 resources using zeolite‐based catalysts to meet emerging energy and environmental demands is also presented. Abstract : Zeolite catalysts play a pivotal role in C1 chemistry including conversion of CO, CO2, CH4, CH3 OH, and HCOOH into various hydrocarbons (e.g., methane, lower olefins, aromatics, and liquid fuels) and oxygenates (e.g., methanol, dimethyl ether, formic acid, and higher alcohols) to meet the demand for energy and chemicals as crude oil reserves decline.